Solidifying and hardening method of weathered coal gangue and road application of weathered coal gangue

Through the method of cement slurry coating and coal gangue curing agent spraying, the weathered coal gangue is cured and hardened, which solves the difficulty of weathered coal gangue in cement pavement, significantly improves its strength and durability, and realizes resource utilization The effect of utilizing and reducing paving costs.

CN119390374APending Publication Date: 2025-02-07JILIN JIANZHU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411228887.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Weathered coal gangue is difficult to apply on a large scale in cement pavement due to its high crushing value and low density.

Method used

The surface spraying method of cement slurry slurry and coal gangue curing agent is used to cure and harden the weathered coal gangue to improve its strength and durability.

Benefits of technology

It significantly improves the strength and durability of weathered coal gangue, overcomes the defects of high crush value and low density, and achieves the purpose of resource utilization and reducing the cost of cement paving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390374A_ABST
    Figure CN119390374A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of pavement surface materials, in particular to a curing and hardening method of weathered coal gangue and road application of the weathered coal gangue. The curing and hardening method of the weathered coal gangue comprises the following steps: preparing cement paste, coating the weathered coal gangue with the cement paste, spraying a curing agent, and curing to obtain the cured weathered coal gangue. Python and Abaqus are combined to establish a fine analysis model of a cement pavement stacking structure, the filling particle size range of the consolidated weathered coal gangue is determined based on an aggregate bearing contribution rate index, and a composition scheme of the consolidated weathered coal gangue cement pavement material is designed; according to the scheme, the treated consolidated weathered coal gangue, gravel, river sand, cement and water are uniformly stirred, and the weathered coal gangue cement pavement is obtained through maintenance. The weathered coal gangue solidifying and hardening method can improve the strength and durability of the weathered coal gangue, so that resource utilization of the weathered coal gangue is realized, the paving cost of a cement pavement is reduced, and sustainable development of coal enterprises is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road surface materials, and in particular to a method for curing and hardening weathered coal gangue and a road application thereof. Background Art

[0002] Gangue is a waste product from coal mining and processing. Due to the huge amount of emissions and low utilization rate, a large amount of gangue is stored in the open air, forming numerous gangue yards. These yards not only occupy a large amount of land, but also the long-term storage of gangue disintegrates and oxidizes under the influence of environmental factors, forming weathered gangue. Weathered gangue contains a large amount of harmful substances, which can cause environmental pollution, spontaneous combustion, erosion and instability of yard structures, posing a threat to the safety of residents' lives and the normal operation of coal enterprises. Therefore, strengthening the comprehensive utilization and management of weathered gangue, improving its utilization rate, and reducing the stockpile volume have become issues that need to be urgently addressed.

[0003] Weathered coal gangue is used in cement pavement, which can not only consume a large amount of weathered coal gangue, but also reduce the paving cost of cement pavement. However, weathered coal gangue has the defects of high crushing value and low density due to the long-term influence of environmental factors such as sunshine and wind, making it difficult to be widely used in cement pavement. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for solidifying and hardening weathered coal gangue and its road application. The weathered coal gangue is solidified and hardened by combining cement slurry wrapping with surface spraying of coal gangue curing agent, which significantly improves its strength and durability, overcomes the defects of high pressure crushing value and low density of weathered coal gangue, and not only realizes the resource utilization of weathered coal gangue, but also reduces the cost of cement pavement paving, thereby promoting the sustainable development of coal enterprises.

[0005] In order to achieve the above purpose, the technical solution adopted in this application is:

[0006] One of the purposes of the present invention is to provide a method for curing and hardening weathered coal gangue, comprising the following steps:

[0007] (1) Mixing cement, water and magnesium aluminum silicate to prepare cement paste; wherein the cement paste prepared by cement, magnesium aluminum silicate and water is used to solidify the surface of weathered coal gangue, and magnesium aluminum silicate is added to prevent water precipitation of cement when the cement and weathered coal gangue are mixed and left to stand;

[0008] (2) soaking the weathered coal gangue in cement slurry and then air-drying it, and coating the weathered coal gangue with cement slurry to obtain air-dried weathered coal gangue;

[0009] (3) After spraying the coal gangue curing agent on the surface of the air-dried and weathered coal gangue, indoor curing is carried out. The coal gangue curing agent is used to solidify and harden the air-dried and weathered coal gangue to obtain consolidated weathered coal gangue.

[0010] Preferably, in step (1), the mass ratio of water to cement is 3-4:4, and the mass ratio of magnesium aluminum silicate to cement is 1-2:100.

[0011] Preferably, in step (2), the weathered coal gangue is immersed in cement slurry, and after being fully immersed, the weathered coal gangue is taken out and air-dried until the cement slurry on the surface of the weathered coal gangue solidifies;

[0012] Among them, the immersion time of weathered coal gangue in cement slurry shall not be less than 30 minutes, and the air-drying time shall not be less than 24 hours.

[0013] Preferably, in step (3), the weathered coal gangue curing agent is a lithium-based curing agent dilution; the mass ratio of the coal gangue curing agent to the air-dried weathered coal gangue is 1 to 2:100;

[0014] Among them, the weathering time of weathered coal gangue is 1 to 3 years, the mass percentage of SiO2 is not less than 50%, the mass percentage of mud is not less than 10%, and the crushing value is greater than 20%.

[0015] Preferably, the gangue solidifying agent is sprayed onto the surface of the air-dried weathered gangue twice, air-dried for 60 minutes after the first spraying, and left at room temperature after the second spraying, and cured for 3 days in an environment of 98% humidity to obtain consolidated weathered gangue.

[0016] The second object of the present invention is to provide the application of the above-mentioned consolidated weathered coal gangue in the preparation of consolidated weathered coal gangue cement pavement material, which is implemented according to the following steps:

[0017] (1) Based on the strength and road grade requirements, the interference grading design theory is used to determine the initial grading form and optimal mix ratio of the cement pavement;

[0018] (2) Establish a numerical simulation model of the initial design gradation, understand the load transfer law of the pavement accumulation structure, and obtain the filling particle size range of consolidated weathered coal gangue;

[0019] (3) mixing consolidated weathered coal gangue and crushed stone within a particle size range to obtain a mixture;

[0020] (4) The mixture prepared in step (3) is mixed with cement mortar, and then maintained to maintain moisture, thereby obtaining a consolidated weathered coal gangue cement pavement material.

[0021] Preferably, in the step (2), the input file of the Abaqus finite element calculation software is written using the python language to achieve random placement and attribute assignment of polygonal aggregates, build a refined analysis model of the cement pavement accumulation structure, calculate the load-bearing contribution rate of each aggregate under load, and determine the filling particle size range of the consolidated weathered coal gangue.

[0022] Preferably, in step (2), the filling particle size of the consolidated weathered coal gangue is 2.36 mm to 19.0 mm, the particle size of the crushed stone is 19.0 mm to 31.5 mm, and the stirring time is 2.0 min to 2.5 min.

[0023] Preferably, in step (4), the cement mortar is mixed with water, cement, river sand and water reducing agent, and the mass ratio of water, cement, river sand and water reducing agent is 120:315:521:3.15, the stirring time is 2min to 2.5min, the curing humidity requirement is not less than 98%, and the curing time is not less than 14 days.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention provides a method for solidifying and hardening weathered coal gangue, and the preparation method can effectively improve the strength and durability of weathered coal gangue. The weathered coal gangue is immersed in the cement slurry for slurry treatment by mixing cement, water and magnesium aluminum silicate, and then the coal gangue curing agent is sprayed on the surface after being taken out and air-dried, and then the weathered coal gangue is obtained through indoor curing.

[0026] 2. The present invention uses weathered coal gangue as raw material to produce consolidated weathered coal gangue, and the consolidated weathered coal gangue and crushed stone constitute aggregate for filling cement pavement, thereby achieving the purpose of resource utilization of weathered coal gangue and cost reduction and efficiency improvement of cement pavement paving.

[0027] 3. The results show that the crushing index of the consolidated weathered coal gangue prepared in Examples 1 to 4 of the present invention is significantly improved compared with that of weathered coal gangue. The crushing indexes measured in the test far exceed the crushing index (25%) of the highway surface concrete Class II gravel required by the "Technical Specifications for Highway Cement Concrete Pavement Construction" (JTG / T F30-2014). Examples 2 to 4 meet the crushing index of the highway surface concrete Class I gravel required by the "Technical Specifications for Highway Cement Concrete Pavement Construction" (JTG / TF30-2014). The crushing index of the consolidated weathered coal gangue fully meets the strength requirements of the specification for highway surface concrete aggregates;

[0028] The weathered coal gangue cement pavement material prepared by the present invention meets the flexural strength requirements of the "Highway Cement Concrete Pavement Design Code" (JTG D40-2011) for medium traffic load levels, and also meets the compressive strength, splitting tensile strength, cohesion and internal friction angle requirements of secondary highways with medium traffic loads. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart of a method for curing and hardening weathered coal gangue and a method for curing weathered coal gangue cement pavement material according to an embodiment of the present invention;

[0030] Figure 2 The crystal structure information diagrams of weathered coal gangue before and after treatment of the present invention, (a) is the crystal structure information diagram of weathered coal gangue, (b) is the crystal structure information diagram of consolidated weathered coal gangue;

[0031] Figure 3 The microstructure diagrams of weathered coal gangue before and after treatment of the present invention, (a) (b) (c) are microstructure diagrams of weathered coal gangue, (a) is magnified by 50 μm, (b) is magnified by 10 μm, (c) is magnified by 2 μm; (e) (f) (g) are microstructure diagrams of consolidated weathered coal gangue, (e) is magnified by 50 μm, (f) is magnified by 10 μm, (g) is magnified by 2 μm;

[0032] Figure 4 This is the particle size distribution diagram of weathered coal gangue of the present invention;

[0033] Figure 5 This is a microscopic model diagram of consolidated weathered coal gangue concrete obtained by consolidating weathered coal gangue according to Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods. The weathered coal gangue used in the present invention is taken from the coal gangue yard of the Jilin Coal Energy Reserve Base in Jilin Province.

[0036] The present invention significantly reduces the crushing index of weathered coal gangue, and the weathered coal gangue after solidification is successfully applied to cement pavement. As shown in Table 4, the crushing index is significantly reduced; Table 6 shows that the density and mechanical properties of the consolidated weathered coal gangue are improved. Practical application also confirms that the consolidated weathered coal gangue prepared by the present invention has a low crushing value, high density, and high compressive and tensile strength.

[0037] The present invention significantly improves the Vickers hardness of weathered coal gangue after freeze-thaw cycles, and the weathered coal gangue after solidification is successfully applied to cement pavement. As shown in Table 5, the Vickers hardness of the weathered coal gangue after solidification is significantly higher than that of the weathered coal gangue without solidification treatment.

[0038] The present invention provides a method for solidifying and hardening weathered coal gangue, such as Figure 1 As shown, the technical solution of the present invention is further explained by using embodiments and comparative examples, as shown below:

[0039] Example 1

[0040] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.075 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 6 kg water;

[0041] A method for curing and hardening weathered coal gangue comprises the following steps:

[0042] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0043] Among them, the mass ratio of water to cement is 3:4; the mass ratio of magnesium aluminum silicate to cement is 1.5:100;

[0044] (2) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 30 minutes, taking out and air-drying for 24 hours to obtain air-dried weathered coal gangue;

[0045] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0046] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0047] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for curing for 3 days.

[0048] Example 2

[0049] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.075 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 6 kg water;

[0050] A method for curing and hardening weathered coal gangue comprises the following steps:

[0051] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0052] Among them, the mass ratio of water to cement is 3:4; the mass ratio of magnesium aluminum silicate to cement is 1.5:100;

[0053] (2) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 30 minutes, taking out and air-drying for 24 hours to obtain air-dried weathered coal gangue;

[0054] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0055] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0056] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for 6 days.

[0057] Example 3

[0058] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.075 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 6 kg water;

[0059] A method for curing and hardening weathered coal gangue comprises the following steps:

[0060] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0061] Among them, the mass ratio of water to cement is 3:4; the mass ratio of magnesium aluminum silicate to cement is 1.5:100;

[0062] (2) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 30 minutes, taking out and air-drying for 24 hours to obtain air-dried weathered coal gangue;

[0063] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0064] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0065] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for curing for 13 days.

[0066] Example 4

[0067] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.075 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 6 kg water;

[0068] A method for curing and hardening weathered coal gangue comprises the following steps:

[0069] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0070] Among them, the mass ratio of water to cement is 3:4; the mass ratio of magnesium aluminum silicate to cement is 1.5:100;

[0071] (5) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 30 minutes, taking out and air-drying for 24 hours to obtain air-dried weathered coal gangue;

[0072] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0073] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0074] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for curing for 27 days.

[0075] Example 5

[0076] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.05 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 7.25 kg water;

[0077] A method for curing and hardening weathered coal gangue comprises the following steps:

[0078] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0079] Among them, the mass ratio of water to cement is 1:1; the mass ratio of magnesium aluminum silicate to cement is 1:100;

[0080] (2) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 25 minutes, taking out and air-drying for 36 hours to obtain air-dried weathered coal gangue;

[0081] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0082] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0083] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for 6 days.

[0084] Example 6

[0085] The raw materials were weighed according to the following weights: 100 kg weathered coal gangue, 0.1 kg magnesium aluminum silicate, 1 kg lithium-based curing agent, 5 kg cement, and 7.25 kg water;

[0086] A method for curing and hardening weathered coal gangue comprises the following steps:

[0087] (1) mixing cement, water and magnesium aluminum silicate to prepare cement paste, stirring at 20° C. and a stirring speed of 50 rad / min for 2 min to obtain cement paste;

[0088] Among them, the mass ratio of water to cement is 1:1; the mass ratio of magnesium aluminum silicate to cement is 2:100;

[0089] (2) soaking the weathered coal gangue in the cement slurry prepared in step (1), stirring evenly, soaking for 25 minutes, taking out and air-drying for 36 hours to obtain air-dried weathered coal gangue;

[0090] Among them, the stirring time is 2min and the stirring speed is 50rad / min;

[0091] (3) mixing the gangue solidifying agent with water, stirring evenly, and spraying the mixture twice on the surface of the air-dried weathered gangue obtained in step (2) to prepare consolidated weathered gangue;

[0092] Among them, the mass ratio of lithium-based curing agent and water is 1:2.25, the stirring time is 2 minutes, and the stirring speed is 60 rad / min; after the first spraying, it is air-dried for 60 minutes, and after the second spraying, it is placed in an environment of 20°C and 98% humidity for 6 days.

[0093] Comparative Example 1

[0094] The weathered coal gangue is dried, and 100 kg of the weathered coal gangue is weighed.

[0095] The weathered coal gangue used in the above Examples 1 to 4 and Comparative Example 1 was analyzed for oxide composition, element composition, and pore structure. The results are shown in Tables 1 to 3:

[0096] Table 1 Oxide composition of weathered coal gangue

[0097] Oxide composition <![CDATA[Na2O]]> MgO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> <![CDATA[SO3]]> <![CDATA[K2O]]> CaO <![CDATA[TiO2]]> <![CDATA[Fe2O3]]> content(%) 0.98 1.13 26.31 57.24 1.08 4.11 1.86 2.14 4.55

[0098] Table 2 Element composition of weathered coal gangue

[0099]

[0100]

[0101] Figure 2The crystal structure information diagram of weathered gangue before and after treatment of the present invention, (a) (b) (c) is the microstructure diagram of weathered gangue, (a) is magnified 50μm, (b) is magnified 10μm, (c) is magnified 2μm; (e) (f) (g) is the microstructure diagram of consolidated weathered gangue, (e) is magnified 50μm, (f) is magnified 10μm, (g) is magnified 2μm; combined with Table 1 and Table 2, it is found that the mineral composition in weathered gangue is relatively complex, and the main mineral composition is quartz, kaolinite, illite, dolomite, siderite, anorthite and TiO2, among which quartz is the main mineral that provides hardness. Compared with fresh gangue rich in anorthite, a larger part of anorthite in weathered gangue undergoes weathering and is converted into clay minerals such as kaolinite and illite. This process not only weakens the stability and mechanical strength of the gangue structure, but also forms cracks and weak layers that are easy to expand inside the gangue, thereby exacerbating the tendency of weathered gangue to expand and crack. The present invention tightly fills and wraps the original pore and crack system of weathered gangue with hydrated calcium silicate and calcium aluminate generated during the curing and hardening process, and significantly inhibits the disintegration of clay minerals due to water absorption and expansion. In addition, the lithium-based curing agent can penetrate into the concrete matrix and react with the calcium hydroxide in the concrete to generate a dense hydrated calcium silicate gel. These gels not only fill the tiny gaps inside the concrete to form a solid calcium silicate hydrate network, but also promote the process of cement hydration reaction, thereby comprehensively improving the overall strength and durability of weathered gangue.

[0102] Figure 3 This is the microstructure diagram of weathered coal gangue before and after treatment of the present invention. Figure 3 (a) is the microstructure of weathered coal gangue, (b) is the microstructure of consolidated weathered coal gangue; Figure 3 (a) and (b) show that weathered gangue has the characteristics of sparse structure, scaly and layered; there are obvious randomly distributed holes on the surface of weathered gangue, and the continuous holes that are not connected form long cracks and weak surfaces, which make weathered gangue have the unfavorable characteristics of weak strength and low stability; while the surface of consolidated weathered gangue is tightly and evenly wrapped by hydrated calcium silicate, calcium sulfonate and part of Ca(OH)2. The mixture of cement and lithium-based curing agent effectively fills the surface pores of weathered gangue, and under the catalysis of lithium-based curing agent, the "spider web" structure composed of calcium silicate and calcium sulfonate bonds the weak points of crystal rods together, making the cement shell more dense.

[0103] Table 3 Pore structure parameters of weathered coal gangue

[0104] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) Pore ​​diameter of maximum pore volume (nm) Weathered coal gangue 54.5873 0.144079 8.4611 10

[0105] Figure 4 The particle size distribution diagram of weathered coal gangue of the present invention is as follows: Figure 4As shown in the figure, the particle size distribution of weathered coal gangue shows a gradation characteristic, among which the particle size distribution of less than 9.50mm is relatively steep. In the particle size range of 9.50mm to 19.0mm, weathered coal gangue accounts for the highest proportion, reaching 24.65%; while the particle size range of 19.0mm to 31.5mm accounts for the least, only 11.59%. In addition, due to weathering and disintegration caused by long-term stacking, the proportion of particles larger than 31.5mm is also relatively low, at 13.87%; at the same time, a large number of particles with a particle size of less than 2.36mm account for 14.88%. Therefore, before using weathered coal gangue as concrete aggregate, although it does not need additional crushing, its particle size distribution must be adjusted by screening.

[0106] According to the "Highway Engineering Aggregate Test Code" (JTG E42-2005), the crushing index performance test was performed on the consolidated weathered coal gangue of Examples 1 to 4 and the weathered coal gangue of Comparative Example 1. The results are shown in Table 4.

[0107] Table 4 Test results of crushing index of consolidated weathered coal gangue of Examples 1 to 4 and weathered coal gangue of Comparative Example 1

[0108] project Crushing index (%) Comparative Example 1 23.96 Example 1 18.03 Example 2 16.54 Example 3 16.17 Example 4 16.05

[0109] The consolidated weathered coal gangue of Example 1 and the weathered coal gangue of Comparative Example 1 were subjected to freeze-thaw cycle tests. The specific test method was as follows: the consolidated weathered coal gangue of Example 1 and the weathered coal gangue of Comparative Example 1 were soaked in water for 24 hours, then placed in a freeze-thaw cycle box at -20°C ± 5°C for 4 hours, taken out and placed in warm water at 20°C ± 5°C for 4 hours, and one cycle lasted for 8 hours. The Vickers hardness was tested after 0, 5, 10, 15, and 20 freeze-thaw cycles, and the results are shown in Table 5.

[0110] Table 5 Comparison of Vickers hardness test results of weathered coal gangue consolidated in Example 1 and weathered coal gangue in Comparative Example 1 after freeze-thaw cycles

[0111] Freeze-thaw cycles <![CDATA[Vickers hardness of Example 1 (kgf / mm 2 )]]> <![CDATA[Vickers hardness of Comparative Example 1 (kgf / mm 2 )]]> 0 113.52 84.32 5 109.76 65.24 10 106.49 54.53 15 103.56 49.37 20 101.93 45.60

[0112] It can be clearly seen from the above data that the consolidated weathered coal gangue prepared in Examples 1 to 4 of the present invention has a significantly improved crushing index compared to weathered coal gangue, and significantly improves the durability of consolidated weathered coal gangue. The crushing indexes measured in the test far exceed the Class II crushing index (25%) of the highway surface concrete required by the "Technical Specifications for Highway Cement Concrete Pavement Construction" (JTG / T F30-2014). The consolidated weathered coal gangue prepared in Examples 2 to 4 meets the Class I crushing index of the highway surface concrete required by the "Technical Specifications for Highway Cement Concrete Pavement Construction" (JTG / T F30-2014), and its crushing index fully meets the strength requirements of the specification for highway surface concrete aggregates. The test shows that the Vickers hardness of Example 1 after 0, 5, 10, 15 and 20 freeze-thaw cycles is increased by 34.63%, 68.24%, 95.29%, 109.76% and 123.53% respectively compared with that of Comparative Example 1. The durability of the consolidated weathered coal gangue prepared in Example 1 is significantly improved, meeting the requirements for use as coarse aggregate.

[0113] Examples 1 to 4 of the present invention all obtained consolidated weathered coal gangue, and the effects were similar. Taking the consolidated weathered coal gangue obtained in Example 2 as an example, the consolidated weathered coal gangue was applied to weathered coal gangue cement pavement materials and studied:

[0114] (1) Based on the strength and road grade requirements, the interference grading design theory is used to determine the initial grading form and optimal mix ratio of the cement pavement;

[0115] (2) The input file of Abaqus finite element calculation software was written using Python language to realize the random placement and attribute assignment of polygonal aggregates, build a refined analysis model of cement pavement accumulation structure, calculate the load contribution rate of each aggregate under load, and determine the filling particle size range of the consolidated weathered coal gangue, as shown in Table 5 and Figure 5 As shown. After assigning actual parameters to each unit, the load contribution rate of each aggregate under load is simulated and calculated to determine the filling particle size range of consolidated weathered coal gangue;

[0116] Among them, the filling particle size of consolidated weathered coal gangue is 2.36mm~19.0mm;

[0117] (3) mixing consolidated weathered coal gangue and crushed stone within a particle size range to obtain a mixture;

[0118] The particle size of the crushed stone is 19.0 mm to 31.5 mm; the stirring time is 2 min, and the stirring speed is 60 rad / min;

[0119] The mass ratio of consolidated weathered coal gangue with different particle sizes is 2.36mm~4.75mm:4.75mm~9.50mm:9.50mm~19.0mm=1:1.4:1.98;

[0120] (4) mixing the mixture prepared in step (3) with cement mortar, and performing moisture maintenance to obtain a consolidated weathered coal gangue cement pavement material;

[0121] The cement mortar is made of water, cement, river sand and water reducing agent, and the mass ratio of water, cement, river sand and water reducing agent is 120:315:521:3.15; the stirring time is 2 minutes, and the stirring speed is 60 rad / min;

[0122] The curing humidity requirement is not less than 98%, and the curing time is 14 days.

[0123] Figure 5 This is a mesoscopic model diagram of consolidated weathered coal gangue concrete obtained by using Example 2 of the present invention. The results show that by writing a script in Python, the model can be directly imported into the Abaqus finite element software for calculation, and the obtained model is highly similar to the internal structure of the actual consolidated weathered coal gangue concrete. The model can meet the random placement of aggregates of various particle sizes according to the actual particle size gradation design. Therefore, the constructed mesoscopic model of consolidated weathered coal gangue concrete is effective.

[0124] The present invention also uses weathered coal gangue as a control sample for research, which is the same as the preparation method of the above-mentioned consolidated weathered coal gangue cement pavement material, except that the consolidated weathered coal gangue in Example 2 is replaced by weathered coal gangue.

[0125] Table 6 Parameters of consolidated weathered coal gangue concrete

[0126]

[0127] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the mechanical properties of the consolidated weathered coal gangue cement pavement material prepared by the present invention were tested, and the results are shown in Table 7.

[0128] Table 7 Mechanical properties of consolidated weathered coal gangue cement pavement materials

[0129]

[0130] It can be clearly seen from the above data that the consolidated weathered coal gangue cement pavement material prepared by the present invention meets the flexural strength requirements (>4.5MPa) for medium traffic load levels in the "Highway Cement Concrete Pavement Design Code" (JTG D40-2011), and at the same time meets the compressive strength requirements (>25MPa) for secondary roads. The code does not have specific requirements for splitting tensile strength, cohesion and internal friction angle, but according to relevant research, the splitting tensile strength, cohesion and internal friction angle of the consolidated weathered coal gangue cement pavement material prepared by the present invention meet the needs of secondary roads with medium traffic load levels.

[0131] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0132] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for solidifying and hardening weathered coal gangue, characterized in that: The following steps are involved: Mixing cement, water and magnesium aluminum silicate to prepare cement paste; soaking the weathered coal gangue in cement paste and then air-drying it to obtain air-dried weathered coal gangue; After the gangue solidifying agent is sprayed on the surface of the air-dried weathered gangue, indoor curing is carried out to obtain consolidated weathered gangue.

2. The method for solidifying and hardening weathered coal gangue according to claim 1, characterized in that: The mass ratio of water to cement in cement paste is 3-4:4, and the mass ratio of magnesium aluminum silicate to cement is 1-2:

100.

3. The method for solidifying and hardening weathered coal gangue according to claim 1, characterized in that: The weathered coal gangue is immersed in cement paste, taken out after being fully immersed, and air-dried until the cement paste on the surface of the weathered coal gangue is solidified; wherein, the immersion time of the weathered coal gangue in the cement paste is not less than 30 minutes, and the air-drying time is not less than 24 hours.

4. The method for solidifying and hardening weathered coal gangue according to claim 1, characterized in that: The gangue curing agent is a lithium-based curing agent; The mass ratio of the gangue curing agent to the slurry-coated weathered gangue is 1 to 2:100, wherein the weathering time of the weathered gangue is 1 to 3 years, the mass percentage of SiO2 is not less than 50%, the mass percentage of mud is not less than 10%, and the crushing value is greater than 20%.

5. The method for solidifying and hardening weathered coal gangue according to claim 1, characterized in that: The gangue curing agent is sprayed twice onto the surface of the air-dried and weathered gangue; After the first spraying, the mixture is air-dried for 50 to 70 minutes. After the second spraying, the mixture is placed at room temperature and cured in an environment of 98% humidity to obtain consolidated weathered coal gangue.

6. Consolidated weathered coal gangue obtained by the solidification and hardening method according to any one of claims 1 to 5.

7. Use of the consolidated weathered coal gangue according to claim 6 in preparing consolidated weathered coal gangue cement pavement material.

8. The use according to claim 7, characterized in that: The consolidated weathered coal gangue cement pavement material is prepared according to the following steps: According to the strength and road grade requirements, the interference gradation design theory is used to determine the initial gradation form and optimal mix ratio of the cement pavement; Establish a numerical simulation model of the initial design gradation, understand the load transfer law of the pavement accumulation structure, and obtain the filling particle size range of consolidated weathered coal gangue; The consolidated weathered coal gangue meeting the particle size range is mixed with crushed stone to obtain a mixture; After the mixture is mixed with cement mortar, moisture is maintained and maintained to obtain a consolidated weathered coal gangue cement pavement material.

9. The use according to claim 7, characterized in that: The input file of Abaqus finite element calculation software is written using Python language to realize the random placement and attribute assignment of polygonal aggregates, build a refined analysis model of cement pavement accumulation structure, calculate the load contribution rate of each aggregate under load, and determine the filling particle size range of the consolidated weathered coal gangue; The filling particle size of consolidated weathered coal gangue is 2.36mm~19.0mm, and the particle size of crushed stone is 19.0mm~31.5mm.

10. The use according to claim 9, characterized in that: The random placement and attribute assignment process of polygonal aggregates includes polygon target edge cutting, model parameter initial function generation, positioning vertex coordinate generation, collision checking, and boundary condition judgment.